Kirk-Othmer Encyclopedia of Chemical Technology 2016
DOI: 10.1002/0471238961.koe00013
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Superwettability Materials

Abstract: Naturally occurring structures such as spider silks, cactus spine, dandelion pappi, lotus leaves, butterfly wings, rose petals, gecko feet, and desert beetles possess unique properties and outstanding wettability characteristics, which are not yet well understood, but may provide inspiration for construction of superwettability materials. The focus of this article is on recent progress in application of bioinspired superwettability materials for diverse uses ranging from nanofibers, self‐cleaning materials, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 180 publications
0
2
0
Order By: Relevance
“…Following Berg's limits based on the measurements of hydrophobic forces [50,51], it can be concluded that the Ti/Zr/Ti/Si and Ti/Cu/Ti/Si thin films are supported by hydrophobic forces and are less water wettable. Due to the energetically beneficial displacement of solutes from the solution into the interphase between solid and solute phases, hydrophobic surfaces facilitate the adsorption of various surfactants and proteins from water [52]. When important measures of biological activity responsive to interfacial phenomena are related to the water adhesion tension of the contacting surfaces, it becomes clear that the physicochemical properties of the interfacial water have a strong influence on the biological response to materials.…”
Section: Resultsmentioning
confidence: 99%
“…Following Berg's limits based on the measurements of hydrophobic forces [50,51], it can be concluded that the Ti/Zr/Ti/Si and Ti/Cu/Ti/Si thin films are supported by hydrophobic forces and are less water wettable. Due to the energetically beneficial displacement of solutes from the solution into the interphase between solid and solute phases, hydrophobic surfaces facilitate the adsorption of various surfactants and proteins from water [52]. When important measures of biological activity responsive to interfacial phenomena are related to the water adhesion tension of the contacting surfaces, it becomes clear that the physicochemical properties of the interfacial water have a strong influence on the biological response to materials.…”
Section: Resultsmentioning
confidence: 99%
“…Nepenthe’s pitcher leaves exhibit a “slippery liquid-infused porous surface” (SLIPS) based on a different mechanism from the superhydrophobic lotus leaf. Nepenthe leaves have microtextured peristomes or rims filled with an intermediary liquid. , The trapped liquid cushion on the pitcher plant surface repels immiscible liquids of almost any surface tension. It makes the surface very slippery to insects.…”
Section: Self-healing Natural Superwetting Surfacesmentioning
confidence: 99%